Comparative Lipidome and Transcriptome Provide Novel Insight Into Polyunsaturated Fatty Acids Metabolism of the Sea Urchin - Wang, Heng; Zhao, Wenfei; Liu, Xiaoyu; Gang, Debao; Zuo, Rantao; Han, Lingshu; Chang, Yaqing; Ding, Jun (Frontiers in Marine Science, 2022)
The sea urchin Strongylocentrotus intermedius is one of the most economically important echinoids harvested from northeast Pacific Ocean coastal waters. The gonads of sea urchins have high nutritional value and are primarily a candidate source of polyunsaturated fatty acids (PUFA). PUFAs are essential for human health, and the biological synthesis and industry production of PUFA have attracted more and more attention from the scientific community. Moreover, PUFAs are important necessary nutrients that determine not only the nutritional value of sea urchins but guarantee their normal growth and reproduction. In this study, we divided 178 sea urchins into three groups (high, medium, and low concentration PUFA groups) according to the concentration of PUFAs, and conducted integrative lipidomics and transcriptomics analyses of different PUFA abundances of S. intermedius to determine the critical genes related to PUFA metabolism in sea urchin gonads. Illumina sequencing generated 894,295,712 clean reads (133.28 Gb) in 18 cDNA libraries. Among all of the unigenes, nine up- and seven down-regulated unigenes were found in a comparison of the “high vs low” concentration PUFA groups of gonads. Interestingly, we found that tudor domain-containing protein 3 (TDRD3) was up-regulated in the high concentration PUFA group, and this gene was significantly related to eicosapentaenoic acid (EPA) in the correlation analysis (p<0.05), and may be used as a candidate marker for EPA biosynthesis and metabolism in the sea urchin. The lipidome and transcriptome information will provide a basic resource for further studies designed to elucidate the molecular mechanism of PUFA metabolism in marine invertebrates, and act as a valuable resource for the practical applications and regulation of the sea urchin aquaculture industry in the future.